FAMILY AWARENESS OF THE METHODS OF ORAL AND DENTAL HEALTHCARE FOR 5-16 -YEAR-OLD CHILDREN WITH DISABILITIES - Burhan M. Hamadneh; Wael N. Almogbel; Mater H. Mahnashi (The Indonesian Journal of Public Health, 2023)
Introduction: Over half of disabled children (53%) suffer from oral and dental health problems (Alwadi et al., 2022) due to poor attention from healthcare providers. Aims: Determine the level of family awareness of oral and dental healthcare methods for 5-16-year-old disabled children in Saudi Arabia. Methods: To achieve the study objective, the descriptive method by the social survey method was used. The required ethical approvals of centers and associations caring for people with disabilities in the region were obtained. These centers cooperated in publishing the study tool through social media applications; the questionnaire link was distributed to a sample of (312) parents of children aged 5-16 years with disabilities in Najran region, south of the Kingdom of Saudi Arabia, in October and November of 2022. Results: There was a weak level of family awareness of the methods of oral and dental healthcare for children aged 5-16 years with disabilities. Also, statistically significant differences at α = 0.05 were found in the level of family awareness of the methods of oral and dental healthcare for children aged 5-16 years with nature of the relationship with the child disability in favor of mothers and the academic qualification in favor of the university academic qualification. Nevertheless, the respondents’ answers did not differ by their child’s type of disability.  Conclusion: The study recommended developing a comprehensive national strategic plan supervised by the Ministry of Health and the Ministry of Social Development to reduce the risk of oral and dental diseases.